Diversity of Fish Parasites in Assam: Discovery and Description of a New Procamallanus Species Infecting Ailia coila - Keisham Lebanan; Naorem Mohilal (Research Perspective on Biological Science Vol. 2, 2025)
Assam, located in northeast India, is home to rich aquatic resources that sustain local fisheries and contribute significantly to food security and livelihoods. However, fish populations in the region are often hosts to various parasites, impacting both aquatic health and public well-being. This study focuses on helminth parasites affecting fish species in the Barak Valley, Assam, particularly the nematodes of the genus Procamallanus. During an extensive parasitological survey, a new species of nematode, Procamallanus (Spirocamallanus) ailiosus n. sp. was discovered in Ailia coila from the Barak River. Morphological analysis was conducted using light microscopy, revealing distinguishing characteristics such as a barrel-shaped buccal capsule with unequal cuticular expansion, 9–10 spiral ridges, and a uniquely structured caudal region. Males exhibited 13 pairs of caudal papillae and a single spicule, while females displayed post-equatorial vulvae with embryonated eggs. The species was compared to existing Procamallanus members, highlighting key morphological distinctions from closely related taxa such as P. (S.) nainitalensis and P. gomtii. Prevalence, abundance, mean density, and infection indices were calculated, with a prevalence rate of 50% in the examined fish. The findings underscore the importance of studying fish parasites in Assam, given their ecological and economic implications. This newly described species expands the knowledge of helminth biodiversity and highlights the necessity of sustainable fisheries management. Further research is required to assess the pathogenic impact of P. (S.) ailiosus n. sp. on local fish populations and its potential consequences for human health.